RESPON JUMLAH TANAMAN PER LUBANG TERHADAP HASIL BEBERAPA VARITAS BUNCIS (Phaseolus vulgaris, L.) TIPE TEGAK - Amifta Chusnia Fajriyah; Gembong Haryono; Historiawati Historiawati (JURNAL VIGOR, 2018)
This researchis about respons plant number of each planting hole on many varieties of peach bean (Phaseolus vulgaris, L.) indeterminate type was done since February up to May 2018 in Village Ngleses, Sub-distric Candimulyo, Distric Magelang at 434 m als with soil pH 6. The research using methode factorial design random group of two factor, with four repeat. The first factor is plant number of each planting hole, that is one, two and three plant and the second factor is kind of varieties of peach bean there are Balitsa 1 and Balitsa 3. The result from the experiment shawing that enhancement plant number of each planting holecan increasing of plant height, pods number per square meter and pods fresh weight per square meter, but decrease of pods number per plant and pods fresh weight per plant.The Balitsa 1 variety give high yield on pods fresh weight per plant and Balitsa 3 variety give high yield on plant height and the age offlowering is more fast. Plant number of each planting hole and varieties kind is not affect each other, so give a separate influence without  interaction